Investigating the factors influencing customer loyalty and the mediating effect of customer satisfaction in online food delivery services: empirical evidence from an emerging market - Kazi Omar Siddiqi; Junaid Rahman; Tipon Tanchangya; Hafizur Rahman; Miguel Angel Esquivias; Md. Hasanur Rahman (Cogent Business & Management, 2024)
This study investigates the factors affecting customer loyalty and the mediating role of customer satisfaction in online food delivery services (OFDS) in Bangladesh. An analysis of 300 responses via structural equation modeling (SEM) revealed that perceived food and service quality alone did not significantly impact customer loyalty. While these qualities are essential, they must enhance customer satisfaction in order to boost loyalty. Significant relationships exist among perceived price, ease of payment, time efficiency, and customer loyalty, with customer satisfaction acting as a crucial mediator. Strategies focusing on pricing, payment convenience, and timely delivery are the most effective for building loyalty. The interplay between perceived quality, pricing, payment, and delivery efficiency enhances the overall customer experience. This study contributes to the literature by applying Attribution Theory and the Technological Acceptance Model (TAM), emphasizing external factors such as pricing, delivery, and payment ease as key loyalty drivers. The findings suggest that OFDS businesses should prioritize reasonable pricing, efficient payment systems, and timely delivery to foster loyalty. Combined with high-quality food and services, these strategies can enhance customer satisfaction, promote business growth, and increase revenue.